Evaluation of Dental Anxiety and Fear in Patients who Admitted to the Faculty of Dentistry: Which Patients are More Risky in terms of Dental Anxiety - Yakar, Burkay; Kaygusuz, Turkkan Ozturk; Pirincci, Edibe (Jimma Univ, Ethiopia, 2019)
Background: Dental anxiety and fear make the dental operation and the treatment difficult. Beside that it causes the delays or absence in the dental appointments so it leads to problems for oral and dental health. The aim of this study was to investigate the frequency of dental anxiety, the factors affecting dental anxiety and the effects of dental anxiety on oral dental health of the participants. Methodology: We conducted a hospital-based, cross-sectional study among 342 patients attending the outpatient clinic of a tertiary dentistry hospital. Dental anxiety and trait anxiety levels of the participants measured using MDAS and STAI scales. We conducted the student t-test, One-way Anova and Tukey's post hoc for the analysis of our data. The Pearson's correlation analysis has been used for the analysis of two different quantitative data obtain from MDAS and STAI scales. Results: The age average of 342 participant of our research was 34,41 +/- 11,78. 59,1% of our participants was women. (n=202) Dental anxiety was existing in the 42,1% of the participants (n=144). 56,4% of the participants have had a hard and painful dental treatment experiences. 15,2% of our participants (n=52) had MDAS 19 point or more. Conclusions: High and statistically significant dental anxiety scores have been detected for the patients who are women, housewives, who had uneasy and painful dental treatment stories, who have personel inclinations to the anxiety. Examinations directed to the factors which would increase the dental anxiety, may prevent possible complications and also the risk carried by the patients related to the dental health may be estimated with the help of this kind of examinations.
Keywords: Dental anxiety; MDAS; STAI; dental fear; dental health